Enhancement of paclitaxel-induced breast cancer cell death via the glycogen synthase kinase-3β-mediated B-cell lymphoma 2 regulation - Noh, Kyung Tae; Cha, Gil Sun; Kang, Tae Heung; Cho, Joon; Jung, In Duk; Kim, Kwang-Youn; Ahn, Soon-Cheol; You, Ji Chang; Park, Yeong-Min (BMB reports, 2016)
Glycogen synthase kinase-3β (GSK-3β) is a serine/threonine protein kinase that is known to mediate cancer cell death. Here, we show that B-cell lymphoma 2 (Bcl-2), an anti-apoptotic protein, is regulated by GSK-3β and that GSK-3β-mediated regulation of Bcl-2 is crucial for mitochondrial-dependent cell death in paclitaxel-stimulated cells. We demonstrate that MCF7 GSK-3β siRNA cells are more sensitive to cell death than MCF7 GFP control cells and that in the absence of GSK-3β, Bcl-2 levels are reduced, a result enhanced by paclitaxel. Paclitaxel-induced JNK (c-Jun N-terminal kinase) activation is critical for Bcl-2 modulation. In the absence of GSK-3β, Bcl-2 was unstable in an ubiquitination-dependent manner in both basal- and paclitaxeltreated cells. Furthermore, we demonstrate that GSK-3β-mediated regulation of Bcl-2 influences cytochrome C release and mitochondrial membrane potential. Taken together, our data suggest that GSK-3β-dependent regulation of Bcl-2 is crucial for mitochondria-dependent cell death in paclitaxel-mediated breast cancer therapy.